Faktor penentu penyimpanan rekod yang baik di kalangan peniaga kecil: pengalaman pegawai audit - Noor Dina, Ibrahim (2022)
Record keeping is vital for business as well as for tax purposes. Tax compliance includes keeping complete business records so that tax liability can be determined correctly and in an orderly manner. Therefore, this study attempts to explore the determinant factors that influence the business record-keeping practices of sole proprietorships and partnerships from the perspective of Inland Revenue Board of Malaysia (IRBM)’s audit officers using the Theory of Planned Behaviour. Specifically, the objective of this study is to examine the influence of attitude, subjective norms, perceived behavioural control and taxpayers’ knowledge on taxation towards record-keeping practices from the perspectives of tax auditors. The results of the study found that attitude and perceived behavioural control have a significant influence on business record-keeping practices. Results from the multiple regression analysis indicate that only two independent variables significantly influence the record-keeping practices which are attitude and perceived behavioural control. From a theoretical perspective, this study contributes to the body of knowledge on the record-keeping practices among business taxpayers. The findings of this study would also insist the tax administrator in identifying the factors that influence the taxpayers’ behaviour in record-keeping practices to achieve the Strategic Intent of the IRBM 2021-2025.